Linear densitometry and digital image processing of proximal femur radiographs: implications for archaeological and forensic anthropology. - Macchiarelli, Roberto; Bondioli, Luca (American Journal of Physical Anthropology, 1994)
Adult proximal femur radiographs were used to explore patterns of age- and sex-related proximal femur cancellous bone involution. The study sample consisted of 66 African-American individuals from the Terry collection (33 males and 33 females), ranging in age from 19 to 71 years. Analyses of the radiographs indicate a more pronounced bone density decrease in females; sex- and site-specific structural patterns of proximal femur trabecular bone loss; a high level of individual variability, in which predicted age deviated from real age by as much as 22.26 years for males and 30.78 years for females; a moderate linear correlation with age for all analyzed variables; and an average discrepancy between known and predicted age of 10.34 years for males and 12.71 years for females for the most satisfactory digital image processing analysis parameter. It is concluded that the usefulness of radiographic images of proximal femora in estimating adult age at death has been overestimated.